An Assessment of Readiness of Sri Lankan University and Special Libraries towards Virtual Library Services - Kumarasinghe, B. G. N. (My University, 2010)
Information and Communication Technologies (lCT) have made a dramatic impact on the library and information science. Considering the prime task of a conventional library as a distribution centre of knowledge, ICT has made the task so simple that anyone from anywhere can access these knowledge distribution centres. Library Science and Information Science together with Communication Technology have created digital libraries to form a hypothetical virtual library which physically exists nowhere with closed boundaries but accessible anywhere. Practically this hypothetical library exists in the so called WorId Wide Web commonly known as Internet. Library and Information related services offered to and received from Internet are defined as virtual library services in this research. ...